If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-12=36+4X
We move all terms to the left:
X-12-(36+4X)=0
We add all the numbers together, and all the variables
X-(4X+36)-12=0
We get rid of parentheses
X-4X-36-12=0
We add all the numbers together, and all the variables
-3X-48=0
We move all terms containing X to the left, all other terms to the right
-3X=48
X=48/-3
X=-16
| -8c+4=5 | | n-1=0.286n | | 6z-3z-2z=3 | | Y=275+0.7y | | 7z=49z=7 | | 0=2x-3+5x-4 | | 16h+h-14h+5h=8 | | 20/x=14/6 | | m/5+19=25 | | 8h-h+h=16 | | -3x-44=-39+2x | | n+6=18n=6 | | 56=j/5+63 | | 9(x+4)=33 | | 11r-9r+4=16 | | y/54=30/45 | | 14r-11r-2r+2=5 | | 54/y=30/45 | | -41=z=42 | | 2x+31=43-10x | | 5/6=x/5.5 | | 1w+8=2+2w | | 17b-13b-3=5 | | 5(4x-6)=90 | | 1=b3− 1 | | -38+38x-25x+241+58x=100x | | 13k-3k=10 | | 4+3c=16 | | 2x-7=5x-4x | | 13k−3k=10 | | 8(x-9)=7x-39 | | 20=4d+12 |